2018
DOI: 10.4103/ajts.ajts_135_17
|View full text |Cite
|
Sign up to set email alerts
|

Audit and education: Role in safe transfusion practice

Abstract: BACKGROUND:Auditing and education are the tools for improvement in the transfusion practices. Clinicians are not providing patient's demographic data and medical history to the blood bank that required transfusion. This missing information in blood request forms can lead to transfusion reactions to the patient. So we planned to analyse the blood request forms received at our blood bank and the impact of educational program for the clinicians.METHODS:A total of 6894 blood request forms were received from the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Patient's name, the referring physician's name and gender were the most completed information on the forms evaluated, with 99.0%, 99.0% and 90.3% completion, respectively. Patidar et al found that the highest number of incomplete fields observed (91.42%) varied from second identification (91.03%) to medical officer's name and signature (1.48%) 18 . They also found that 51.44% of forms did not mention urgency of requirements, and pretransfusion haematological parameters were not provided in 53.67% of the request forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient's name, the referring physician's name and gender were the most completed information on the forms evaluated, with 99.0%, 99.0% and 90.3% completion, respectively. Patidar et al found that the highest number of incomplete fields observed (91.42%) varied from second identification (91.03%) to medical officer's name and signature (1.48%) 18 . They also found that 51.44% of forms did not mention urgency of requirements, and pretransfusion haematological parameters were not provided in 53.67% of the request forms.…”
Section: Discussionmentioning
confidence: 99%
“…Osegbe et al educated clinicians about the completion of request forms, and they found significant improvement in the recording of patient age, hospital number, clinician's name, ward, clinical diagnosis and specimen type 22 . Patidar et al found that the most common incomplete column was second identification followed by previous transfusion history and adverse transfusion reactions due to previous transfusion 18 . After education of clinicians and their staff, there were significant improvements in the filling of blood request forms.…”
Section: Discussionmentioning
confidence: 99%
“…Some more info like transfusion history and history of any reactions in previous transfusions are also required for the data to be complete and comprehensive. 25 A complete data shortens the delay of proper blood product issuance. On the other hand, it also provides means to cross-check discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these inappropriate transfusions/reactions due to errors are preventable with improved transfusion practices. Predetermined transfusion guidelines, transfusion audits and training of clinical staff have been shown to improve the transfusion practices [4][5][6]. Clinical audits are an important part of the quality assurance programme which can be used to provide information for improving transfusion medicine practice [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Predetermined transfusion guidelines, transfusion audits and training of clinical staff have been shown to improve the transfusion practices [4][5][6]. Clinical audits are an important part of the quality assurance programme which can be used to provide information for improving transfusion medicine practice [5,6]. Significant reduction of blood component usage can be achieved by auditing with feedback to physicians, a continuous medical education programme for hospital staff, introduction of a request form of blood and component and providing a computerized decision support system [7,8,9].…”
Section: Introductionmentioning
confidence: 99%